Management of Pulmonary Tuberculosis in Liver Cirrhosis: A Case Report - Hadya Gorga; Irvan Medison; Dewi Wahyu F. (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Anti-tuberculosis drugs (OAT) are metabolized in the liver and have a high potential for hepatotoxicity, and will increase the risk of drug-induced liver injury (DILI). This study aimed to describe the management of pulmonary tuberculosis in patients with cirrhosis of the liver. Case presentation: 45 years old male patient with cough with phlegm for 5 months, weight loss. The patient is also known to have cirrhosis of the liver. From the results of the bacteriological examination, it was found that TCM mtb was detected as high. The patient has risk factors for low BMI, a history of alcohol, hypo albumin, and comorbid hepatic cirrhosis. This patient was given a hepatoprotection. After liver function improved, the patient was started on anti-tuberculosis drugs with a regimen of 2 hepatotoxic drugs, namely isoniazid, rifampin, and ethambutol, given gradually and planned to be given for 9 months, with regular monitoring of liver function in the first 2 months. Conclusion: Effective management of pulmonary tuberculosis infection depends on giving OAT at the appropriate dose and duration. The selection of regimen and duration of therapy can be considered based on the condition of chronic liver disease. Careful assessment and periodic evaluation of liver function are required.